Identification of Angiogenesis-Related Gene Signatures and Prediction of Potential Therapeutic Targets in Ulcerative Colitis Using Integrated Bioinformatics - Xu X; Ying H; Wang X; Hong W; Zhang M (Journal of Inflammation Research)
Xijuan Xu,1,* Hongan Ying,2,* Xiaozhi Wang,1 Weiwen Hong,1 Meng Zhang3 1Department of Anus & Intestine Surgery, Taizhou First People’s Hospital, Taizhou, Zhejiang, People’s Republic of China; 2Department of Geriatrics, Taizhou First People’s Hospital, Taizhou, People’s Republic of China; 3Department of General Surgery, Taizhou First People’s Hospital, Taizhou, Zhejiang, People’s Republic of China*These authors contributed equally to this workCorrespondence: Weiwen Hong, Department of Anus & Intestine Surgery, Taizhou First People’s Hospital, No. 218, Hengjie Road, Huangyan District, Taizhou, Zhejiang Province, People’s Republic of China, Tel/Fax +86-15857666675, Email anyway@wmu.edu.cn Meng Zhang Department of General Surgery, Taizhou First People’s Hospital, Taizhou, 318020, People’s Republic of China, Tel +86 15858687813, Email xuzm04@163.comObjective: This study aims to clarify angiogenesis mechanisms in ulcerative colitis and identify potential therapeutic targets.Methods: The Gene Expression Omnibus (GEO) database was used to obtain expression profiles and clinical data for UC and healthy colon tissues. Angiogenesis-related gene sets were acquired from GeneCards. Differential expression analysis and weighted gene co-expression network analysis (WGCNA) identified UC-associated hub genes. The CIBERSORT algorithm assessed immune cell infiltration. Analyses of Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) were performed to determine biological mechanisms. External datasets were utilized to validate and characterize the angiogenesis-related genes in relation to biological agents. Additionally, an ulcerative colitis mouse model was constructed to verify the key genes’ expression using real-time quantitative PCR. To predict potential therapeutic agents, we used the DGIdb database. Molecular docking modeled small molecule binding conformations to key gene targets.Results: This study identified 1,247 DEGs enriched in inflammatory/immune pathways from UC and healthy colon samples. WGCNA indicated the black and light cyan modules were most relevant. Intersecting these with 89 angiogenesis genes revealed 5 UC-associated hub genes (pdgfrb, vegfc, angpt2, tnc, hgf). Validation via ROC analysis, differential expression, and a mouse model confirmed upregulation, supporting their potential as UC diagnostic biomarkers. Bioinformatics approaches like protein–protein interaction, enrichment analysis, and GSEA revealed involvement in PDGFR and PI3K-Akt signaling pathways. CIBERSORT analysis of immune cell infiltration showed positive correlations between the key genes and various immune cells, especially neutrophils, highlighting angiogenesis-inflammation interplay in UC. A ceRNA network was constructed. Drug prediction and molecular docking revealed potential UC therapies like sunitinib and imatinib targeting angiogenesis.Conclusion: This study identified and validated five angiogenesis-related genes (pdgfrb, vegfc, angpt2, tnc, hgf) that may serve as diagnostic biomarkers and drug targets for UC.Keywords: ulcerative colitis, bioinformatics analysis, WGCNA, GSEA, molecular docking